A qualitative study of pain and related symptoms experienced by people with Ehlers-Danlos syndromes - Schubart, Jane R.; Mills, Susan E.; Francomano, Clair A.; Stuckey-Peyrot, Heather (Frontiers in Medicine, 2024)
Introduction Individuals with Ehlers-Danlos syndromes (EDS) often have complex and multi-faceted symptoms across the lifespan. Pain and the related symptoms of fatigue and sleep disorders are common. The objective of this qualitative study was to understand how participants manage their pain and related symptoms. Methods The design was a qualitative thematic content analysis. Twenty-eight interviews were conducted to collect data from individuals who were participants in a prior quantitative longitudinal study. A semi-structured interview guide was designed to focus on and understand the trajectory of pain, sleep, fatigue, and general function. The interview continued with questions about coping mechanisms and obstacles to maintaining a sense of well-being. Results Symptoms reported by participants were widespread and often interwoven. Pain was universal and often resulted in fatigue and disordered sleep which impacted physical function. Most participants reported that their symptoms worsened over time. Participants reported a wide range of effective interventions and most reported developing self-care strategies to adapt to their disabilities/limitations. Solutions included complementary interventions discovered when conventional medicine was unsuccessful. Very few relied on a “system” of health care and instead developed their own strategies to adapt to their disabilities/limitations. Discussion EDS symptoms are often debilitating, and their progression is unknown. For most participants, symptoms worsened over the time. Even though participants in our study, by experience, were self-reliant, the importance of knowledgeable medical providers to help guide self-care should be emphasized.